Can Mohalla Clinics be a Catalyst for Ayushman Bharat Pradhan Mantri Jan Arogya Yojna to achieve Universal Health Coverage in India? - Debraj Mukhopadhyay; Vibhor Dudhraj; Niharika Malhotra; Kritika Jain; Sananda Mishra (International Healthcare Research Journal, 2021)
BACKGROUND: Expenditure on health sector in India is one of the lowest public health expenditures in the world at just over 1% of GDP, with substantial disparities in population, infrastructure, availability and provision of services that define the Indian health care system. In a reform of Indian health systems approved by the Indian Government in March 2018, Ayushman Bharat Pradhan Mantri Jan Arogya Yojana (AB-PMJAY) was launched on 23rd September, 2018 to provide financial health insurance coverage of Rs. 5 lakhs per family per year for secondary and tertiary care hospitalizations to more than 10.74 million poor families that form the bottom 40% of population in India. OBJECTIVES: The objective of this paper is to discuss and analyze the benefits and weaknesses of the AB-PMJAY model and investigating the position that these clinics can play in (I) improving the provision of urban health facilities (II) resolving health inequities (III) and enhancing primary health care. MATERIALS AND METHOD: The authors explored different databases. Government portals, research publications on AB-PMJAY and Mohalla clinics (MC) to do in-depth analysis of various parameters. RESULTS: Although there are significant obstacles to the programme, by building impetus for program reform, AB-PMJAY offers an opportunity for the nation to resolve long-standing and ingrained shortcomings in governance, quality control and stewardship, and to accelerate India’s development towards the stated UHC supply goal. The main achievement of these facilities in the last 18 months has been to introduce wellness to civic and political dialogue. CONCLUSION: Mohalla Clinics can prove as a major catalyst for Ayushman Bharat Pradhan Mantri Jan Arogya Yojna for health reforms and progress towards universal health coverage in India.